IMPROVEMENT OF THE CONSTRUCTION OF THE 2-CHTL STONE CATCHER USED IN THE COTTON CLEANING PLANT (Journal of Science-Innovative Research in Uzbekistan, 2024)
This study focuses on the enhancement of the construction of the 2-CHTL stone catcher utilized in cotton cleaning plants to improve efficiency and productivity. The stone catcher plays a crucial role in removing stones, debris, and other impurities from raw cotton, ensuring product quality and minimizing damage to downstream equipment. By optimizing the design, materials, and operation of the 2-CHTL stone catcher, this research aims to address common challenges such as durability, maintenance, and performance variability. Through innovative design modifications, material upgrades, and integration of advanced technologies, the goal is to develop an improved version of the 2-CHTL stone catcher that enhances cleaning efficiency, reduces downtime, and enhances overall operational effectiveness in cotton processing plants